Development of 15 nuclear microsatellite markers in Deuterocohnia (Pitcairnioideae; Bromeliaceae) using 454 pyrosequencing. (8th May 2018) - Zenk, Fides Lea; Firmer, Cynthia; Wöhrmann, Tina; Silva, Luciana Vicente da; Weising, Kurt; Huettel, Bruno; Paggi, Gecele Matos
Abstract : Premise of the Study: Microsatellite markers were developed in Deuterocohnia longipetala (Bromeliaceae) to investigate species and subspecies boundaries within the genus and the genetic diversity of natural populations. Methods and Results: We used 454 pyrosequencing to isolate 835 microsatellite loci in D. longipetala . Of 64 loci selected for primer design, 15 were polymorphic among 23 individuals of D. longipetala and 76 individuals of the heterologous subspecies D. meziana subsp. meziana and D. meziana subsp. carmineo‐viridiflora . Twelve and 13 of these loci were also polymorphic in one population each of D. brevispicata and D. seramisiana, respectively. Numbers of alleles per locus varied from two to 14 in D. longipetala, two to 12 in D. meziana, one to nine in D. brevispicata, and one to 10 in D. seramisiana . STRUCTURE analyses clearly separated the taxa from each other. Conclusions: The 15 new microsatellite markers are promising tools for studying population genetics in Deuterocohnia species.